Protein Phosphatase-1 - targeted Small Molecules, Iron Chelators and Curcumin Analogs as HIV-1 Antivirals - Lin, Xionghao; Ammosova, Tatyana; Kumari, Namita; Nekhai, Sergei (Current Pharmaceutical Design, 2017)
Background: Despite efficient suppression of HIV-1 replication, current antiviral drugs are not able to eradicate HIV-1 infection. Permanent HIV-1 suppression or complete eradication requires novel biological approaches and therapeutic strategies. Our previous studies showed that HIV-1 transcription is regulated by host cell protein phosphatase-1. We also showed that HIV-1 transcription is sensitive to the reduction of intracellular iron that affects cell cycle-dependent kinase 2. We developed protein phosphatase 1-targeting small molecules that inhibited HIV-1 transcription. We also found an additional class of protein phosphatase-1-targeting molecules that activated HIV-1 transcription and reported HIV-1 inhibitory iron chelators and novel curcumin analogs that inhibit HIV-1. Here, we review HIV-1 transcription and replication with focus on its regulation by protein phosphatase 1 and cell cycle dependent kinase 2 and describe novel small molecules that can serve as future leads for anti-HIV drug development. Results: Our review describes in a non-exhaustive manner studies in which HIV-1 transcription and replication are targeted with small molecules. Previously, published studies show that HIV-1 can be inhibited with protein phosphatase-1-targeting and iron chelating compounds and curcumin analogs. These results are significant in light of the current efforts to eradicate HIV-1 through permanent inhibition. Also, HIV-1 activating compounds can be useful for “kick and kill” therapy in which the virus is reactivated prior to its inhibition by the combination antiretroviral therapy. Conclusion: The studies described in our review point to protein phosphatase-1 as a new drug target, intracellular iron as subject for iron chelation and novel curcumin analogs that can be developed for novel HIV-1 transcription- targeting therapeutics.
Keywords: HIV-1